The value of prebent reconstruction plates and in-house 3D printing - Kühle, Reinald; Kübler, Medea; Fuchs, Jennifer; Bouffleur, Frederic; Moratin, Julius; Freier, Kolja; Engel, Michael; Hoffmann, Jürgen; Ristow, Oliver; Freudlsperger, Christian (Journal of stomatology, oral and maxillofacial surgery, 2023)
Introduction - Reconstruction plates, prebent on 3D printed models, are a cheap, quick, and safe solution to improve mandibular reconstruction procedures. The European Medical Device Regulation has changed recently and severely affects 3D printing in hospitals. Therefore, its legitimation must be discussed. This retrospective observational Case-Control Study aimed to evaluate the impact of prebent reconstruction plates on the condylar position in the temporomandibular joint after continuity resection of the mandible in oncological cases. - Materials and Methods - We included patients who underwent segmental mandibular resection without exarticulation of the condyle or history of prior surgery. The patients were divided into groups with prebent plates on a stereolithographic model and intraoperatively bent reconstruction plates. The segmental defects were categorized using the Jewer Classification. Computed Tomography (CT) scans before and after surgery were analyzed using a standardized method to measure the metric movement of the condyles, as well as their angulation to reference planes to quantify positional changes (primary outcome measures). The influence of the defect location, according to the Jewer classification, was evaluated as a secondary outcome measure. - Results - 73 patients, including 33 with preformed reconstruction plates, were included. We could show significantly fewer rotational deviations in cases of prefabricated osteosynthesis in the coronal plane (p<0,001) and in the sagittal plane (p<0,027). - Discussion - Using preformed reconstruction plates on 3D printed models improves the correct anatomical position of the condyle after mandibular resection. Especially Jewer-class-L defects seem to benefit from individualized reconstruction plates.